Foundations of Applied Statistical Methods - Lee, Hang (Springer International Publishing : Imprint: Springer, 2014)
This is a text in methods of applied statistics for researchers who design and conduct experiments, perform statistical inference, and write technical reports. These research activities rely on an adequate knowledge of applied statistics. The reader both builds on basic statistics skills and learns to apply them to applicable scenarios without over-emphasis on the technical aspects. Demonstrations are a very important part of this text. Mathematical expressions are exhibited only if they are defined or intuitively comprehensible. This text may be used as a self review guidebook for applied researchers or as an introductory statistical methods textbook for students not majoring in statistics. Discussion includes essential probability models, inference of means, proportions, correlations and regressions, methods for censored survival time data analysis, and sample size determination. The author has over twenty years of experience applying statistical methods to study design and data analysis in collaborative medical research setting as well as on teaching. He received his PhD from the Department of Preventive Medicine at the University of Southern California and post-doctoral training at Harvard Department of Biostatistics. Hang Lee has held faculty appointments at the UCLA School of Medicine and Harvard Medical School. He is currently a biostatistics faculty member at Massachusetts General Hospital and Harvard Medical School in Boston, Massachusetts, USA. .